Theoretical Prediction of Possible Drug Treatment of COVID-19 using Coumarin Containing Chloroquine Moeity Compounds - Ibrahim, A.A.; Yahya, O.M.; Ibrahim, M.A. (Asian Journal of Chemistry, 2020)
Chloroquine was theoretically reacted with the coumarin compound. Two compounds viz. [N-(7-chloroquinolin-4-yl)-N-(5-(diethylamino)-pentan-2-yl)-4-methyl-2-oxo-2H-chromene-7-sulfonamide] (3) and [N-(7-chloroquinolin-4-yl)-N-(5-(diethylamino)pentan-2-yl)-4-methyl-2-oxo-2H-chromene-6-sulfonamide] (4) were suggested. The results showed that compound 4 may influence the COVID-19 treatment. The physico-chemical parameters were determined through theoretical calculations by using Hartree-Fock at different basis sets (6-31G), (STO/3G) and the semi-empirical (AM1) method. The calculations demonstrated the scheme of reaction between coumarin and the chloroquine structure by using the predicted mechanisms. The physical and chemical properties of the predicted compounds were determined to select the optimal form as the candidate for COVID-19 treatment. Compound 4 was more stable than compound 3, with different proteins viz. 6YHU, 6YI3 and 6LU7. Three types of software, including Gaussian 03, Chem-Bio office and molecular operating environment (MOE) were employed.